On the Analytical Modeling of a Resonant Fatigue Testing Rig - Chen, Leilei; Xing, Siyuan; Xiong, Xingzhong (Journal of Vibration Testing and System Dynamics, 2026)
The drill string is a common rotating structure extensively used in oil exploration and production. The drill string fails under the long-term action of internal and external pressure, axial force, bending stress and torque in the drilling process. In order to facilitate the study of fatigue life of pipe joints, a light-structural and cost-and-time, efficient resonant bending fatigue test scheme is adopted, an analytical resonant bending fatigue test model is established, and the relationship between the parameters such as pipe length and the natural frequency of the sample is explored. The natural frequency and the zero-displacement position of the first mode of the test sample are predicted. The location of the moving point, the central bending moment and the corresponding normal stress can be used to predict if the test requirements are satisfied.